Um estudo semiótico sobre o slam em Libras: uma nova manifestação artístico-cultural - Silva, Jacqueline Veríssimo Ferreira da (2023)
With the growing artistic and cultural manifestations of the deaf community, there is a demand to expand academic research aimed at analyzing the speeches of deaf people, and in the case of cultural productions of signaled slam, it was perceived that the need is even greater. Signaled slam is a more recent cultural production, which presents themes with contemporary social problems, involving deaf people and which presents a scarcity of studies focused on discourse analysis, specifically based on Greimasian semiotics. With the aim of semiotically analyzing the production process of slam in Libras, having as artistic material the productions of the group ―Slam do Corpo‖. And having as steps to carry out this research, the specific objectives: The identification of the role of the deaf poet, the hearing translator and the hearing poet-translator in these literary productions; The thematic categorization of poetic productions of the Brazilian deaf community recorded in signed slam events in Brazil and; To analyze three (3) poetic texts produced by the group Slam do Corpo based on Greimasian Semiotic and Semiotics os Cultures. To methodologically delineate each proposed step, a qualitative approach was chosen, aiming to highlight the subjective characteristics of poetic works, based on ethnomethodological research. The analysis of the works is inferred from the verbal and non-verbal elements of the deaf people, with the perspective of highlighting determining factors for the identification of divergent social perspectives, between the deaf and hearing people. Despite bringing two different languages into their presentations, Slam do Corpo manages to use them in such a way that there is a linguistic and corporeal uniqueness between them. And analyzing exclusively the texts presented, it is observed that they bring a different perspective, because the external and internal issues that constitute them bring divergent social perspectives of the deaf community and the listener. To subsidize this research the authors base it are: Fiorin, Barros, Batista, Strobel, Peixoto, Machado and Sutton - Spence, Pais.